2004
DOI: 10.1590/s0103-84782004000600015
|View full text |Cite
|
Sign up to set email alerts
|

Variabilidade espacial do pH, Ca, Mg e V% do solo em diferentes formas do relevo sob cultivo de cana-de-açúcar

Abstract: Em uma paisagem natural, os solos apresentam uma ampla variação dos atributos químicos, tanto vertical como horizontal, resultante da interação dos diversos fatores de formação envolvidos. Este trabalho foi desenvolvido em Guariba-SP, com o objetivo de avaliar a variabilidade espacial do pH, cálcio (Ca), magnésio (Mg) e saturação por bases (V%) em um Latossolo Vermelho eutroférrico sob cultivo de cana-de-açúcar, utilizando-se métodos da estatística clássica, análise geoestatística e técnica de interpolação de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
17
0
38

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 20 publications
8
17
0
38
Order By: Relevance
“…The ranges obtained for soil chemical attributes (Table 2) showed wide variation with minimum of 12.02 m for Ca 2+ in the third sampling of Area 1 and maximum of 60.49 m for TN in the first sampling of Area 1. High range values characterize higher continuity in the distribution of the variable, possibly due to the management (Souza et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…The ranges obtained for soil chemical attributes (Table 2) showed wide variation with minimum of 12.02 m for Ca 2+ in the third sampling of Area 1 and maximum of 60.49 m for TN in the first sampling of Area 1. High range values characterize higher continuity in the distribution of the variable, possibly due to the management (Souza et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Solo, 36:1073-1082 moderate (12 % < CV < 60 %). Studies use the CV to assess the spatial variability in the soil properties and report greater spatial variability of chemical and physical properties in concave than in linear or convex curvatures (Souza et al, 2004;Montanari et al, 2008;Souza et al, 2009). Sanchez et al (2009) showed in their work the influence that the water and solution flow, be it surface or subsurface, vertical or horizontal, have on the processes of variability in soil properties.…”
Section: Resultsmentioning
confidence: 99%
“…Esta diversidade de ambientes condiciona diferenças nas propriedades do solo, em especial dos atributos químicos. Atributos químicos do solo são influenciados pela cultura e práticas agrícolas (Silva & Lima, 2012) enquanto a adubação foi apontada como a causa dos elevados valores do CV para P e Mg em estudo desenvolvido por Souza et al (2004).…”
Section: Resultsunclassified